Frequency of intracranial aneurysms and sub-arachnoid hemorrhage is significantly lesser in bicuspid aortic valve than aortic coarctation. (1st May 2021) - Vallabhajosyula, Saarwaani; Vallabhajosyula, Saraschandra; Yang, Li-Tan; Rabinstein, Alejandro A.; Enriquez-Sarano, Maurice; Michelena, Hector I.
Abstract: Background: Bicuspid aortic valve(BAV) is common. Some studies suggest that all BAV patients require screening for intracranial aneurysm(IA) in order to prevent sub-arachnoid hemorrhage(SAH). Aortic coarctation(CoA) carries high-risk of both IA and SAH. Using a nationally-representative population, we assessed the frequency of IA and SAH in admissions with BAV-without-CoA versus admissions with CoA(with or without BAV). Methods: Between 2000 and 2016, adult admissions with a primary/secondary diagnosis of BAV and/or CoA were identified using the National Inpatient Sample. Admissions with traumatic SAH and inter-hospital transfers were excluded. Outcomes were frequency of IA and SAH, and in-hospital mortality in BAV-without-CoA versus CoA. Results: In this 17-year period, 254, 675 admissions met inclusion criteria and 236, 930(93.0%) had BAV-without-CoA. BAV-with-CoA was present in 2846(1.1%) and isolated-CoA in 14, 899(5.9%), for a total of 17, 745(7%) with CoA. IA was noted in 405 admissions(0.2%) overall, BAV-without-CoA versus CoA having 293(0.1%) versus 112(0.6%), p < 0.001. SAH was noted in 910 admissions(0.4%) overall, with BAV-without-CoA versus CoA having 760(0.3%) versus 150(0.9%), p < 0.001. Conclusions: In this study, BAV-without-CoA admissions had 0.1%(6-times lower than CoA) and 0.3%(3-times lower that CoA) IA and SAH, respectively, which is comparable to the general population. This suggests that BAV-without-CoA patients likely do not require routine surveillance for IA. Highlights: First nationally-representative study describing aneurysmal sub-arachnoid hemorrhage(SAH) in bicuspid aortic valve(BAV). We note that CoA admissions exhibited a higher frequency of IA and SAH than BAV without CoA. The most important patient-outcome, frequency of SAH, is comparable to the general population. Our study adds to the growing notion that BAV- without-CoA does not benefit from routine surveillance for IA. Our findings also support ongoing IA screening in patients with CoA.